A hybrid simulated annealing thresholding algorithm for compressed sensing - Fengmin, Xu; Shanhe, Wang (Signal processing, 2013)
In this paper we present a new hybrid simulated annealing thresholding (HSAT) algorithm which preserves the computational simplicity of thresholding algorithm but with the global convergence. We verify the convergence of the new hybrid simulated annealing thresholding algorithm and provide a series of experiments and applications to assess performance of the algorithm. The experiments and applications show that the proposed hybrid algorithm is global convergence and can be accepted as a solver for signal and image reconstruction problems. ► We propose a new hybrid simulated annealing thresholding algorithm. ► We verify the convergence of the algorithm. ► We provide a series of experiments of CS.